IMPACT OF PRINCIPALS' MANAGERIAL ROLES UNDER SCHOOL-BASED MANAGEMENT ON SCHOOL IMPROVEMENT AT URBAN SECONDARY SCHOOLS OF BANGLADESH - Kazi Enamul Hoque; Saedah Siraj; Muhammad Faizalal A. Ghani (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
This article aims al observing the relationship between principals' managerial roles and the improvement of schools and the impacts of principals' managerial roles toward school improvement based on the school-based management. This research uses 127 principals and 694 teachers of urban secondary schools of Bangladesh as the sample. Schools are becoming better when the principals give more emphasizing on strategic plan, supportive and comprehensive roles but less emphasizing on shared decision making. The findings of this study offer valuable information for policy makers and educational managers, especially the principals and teachers. Key words: Principals managerial roles, school-based management, teachers' Professional development activities, school improvement